THE PERFORMANCE OF CONVENTIONAL BANKING AND SHARIA BANKING IN INDONESIA - Sasmita, Anggun Dewi; Anindyntha, Firdha Aksari (Program Studi Ekonomi Pembangunan, 2024)
Indonesia is a country with the largest Muslim population in the world. However, public interest in sharia banking in Indonesia is not as big as conventional banking. This study aims to identify how the performance of conventional banking and Sharia banking differs using the RGEC approach for the 2011-2020 period by looking at the difference test between the two banks. The difference test uses the Paired Sample T-Test and the Wilcoxon test. The findings show that there are performance differences between conventional banking and Sharia banking. The most significant difference is in profitability that using variable of ROA. Furthermore, a second test was carried out using panel regression to determine the factors that can affect the profitability of the two types of banking, using bank internal factors, namely the ratio of NPL or NPF ratio and LDR or FDR and LDR s well as well as external factors, including inflation and interest rates. The findings show that the NPL has a significant negative effect on the profitability of Sharia banks. Meanwhile, LDR has a negative effect on profitability of conventional bank. Interest rates have a positive and significant effect on both conventional and sharia banking, while inflation has no significant effect on the profitability of the two types of banks. These results indicate that both types of banking need to manage banking performance by utilizing interest rate instruments which have a positive impact on increasing profitability